Aplication problems regulated by the EU Succession Regulation - Rodríguez Rodrigo, Juliana (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
In this paper we will explain the three application problems that are covered by the European Succession Regulation. Of the three, the public policy, the remission to States with more than one legal system and the renvoi, the latter is the one that presents a more particular regulation. In effect, the Regulation departs from the general line of excluding this figure, which is followed by the rest of the European Regulations on Private International Law. In addition, the Regulation not only allows it, but also allows it up to the second degree.
Keywords: public policy; states with more than one legal system; renvoi; the EU succession Regulation